Employee Capital Plans as a Means to Improving the Adequacy of Poland’s Pension System - Filiczkowska, Joanna; Jedynak, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The article assesses the impact of employee capital plans (ECP) on the adequacy of pensions in Poland. On the basis of three dimensions of adequacy, the following research questions were formulated: To what extent will ECP affect the growth of future replacement rates in the Polish pension system? Will ECP affect the reduction of poverty of the elderly people in Poland? Will ECP reduce the gender pension gap? An attempt to provide comprehensive answers to these questions is the specific objective of the study.Research Design & Methods: The research methods used include meta-analysis of previous studies, statistical analysis of data published by public institutions, and the analysis of law from an economic perspective. Conclusions are based on inductive reasoning based on the synthesis of the results of the individual research methods.Findings: It is not clear from the research if introducing ECP improves the income adequacy of the Polish pension system, though it may do so narrowly, by smoothing consumption in individual terms. However, taking into account the multidimensional approach to the adequacy of pensions, this solution has proven ineffective. Specifically, ECPs do not contribute to reducing the scale of poverty among pensioners or eliminating gender inequalities.Implications / Recommendations: ECPs should be treated as an instrument for improving the amount of future retirement benefits for a part of society, and not as a tool to effectively improve the multi-dimensional income adequacy of the Polish pension system.Contribution: Examination and assessment of the impact of introducing ECPs on the income adequacy of the Polish pension system.